REALISASI KESANTUNAN BERKOMUNIKASI PADA MEDIA SOSIAL INSTAGRAM @JOKOWI: STUDI POLITIKOPRAGMATIK - Hari Kusmanto Kusmanto; Harun Joko Prayitno; Abdul Ngali; Laili Etika Rahmawati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2019)
Abstract. Politeness is not only related to the act of politeness of language but also related to politics (politeness). This study aims to describe (1) a form of positive politeness; (2) politeness strategies; and (3) politics pragmatic power of positive politeness comments on Jokowi's Instagram account. The data in this study are comments from followers of the Jokowi Instagram account that have positive politeness values. The data source in this study is commenting on followers of the Jokowi Instagram account. Data collection in this study uses the method of note and note, and documentation. Data analysis in this study used intralingual and extralegal methods. The results of the study show (1) the form of positive politeness that the follower chooses the most in commenting is by paying attention to the Regina of the partner. This shows Jokowi's Instagram followers have an optimistic attitude towards Jokowi's leadership. (2) The politeness strategy that is most used by followers in commenting indirectly. This shows that the level of politeness used by Jokowi's Instagram account followers in narrating is already good. (3) The political power of programmatic positive politeness in followers of Instagram accounts includes begging power, praising power, supporting power, influencing power, motivating power, and suggestive power. This shows that followers of the Instagram account have an optimistic attitude towards Jokowi's leadership.